Fabrication of asymmetric nanofiltration flatsheet membrane for the separation of acetic acid from xylose and glucose - Wan Hairani, Wan Na'aman; Syed Mohd Saufi, Tuan Chik; Mazrul Nizam, Abu Seman; Hafizuddin, Wan Yussof; Abdul Wahab, Mohammad (AIDIC Servizi, 2017)
Malaysia palm oil based industries generate a huge amount of lignocellulose biomass wastes. These wastes can be utilized to produce chemicals and fuel. Lignocellulose biomass consists of hemicelluloses, cellulose and lignin. Cellulose and hemicelluloses portion need to be hydrolysed to release fermentable glucose and xylose for further processing. Biomass hydrolysis using acid is a simple method, but it also produces acetic acid inhibitor that can inhibit the microorganism during fermentation. In order to increase the yield of product as well as to elevate the rate of product, there is a need to remove this acetic acid inhibitor from the biomass hydrolysate. In the current study, asymmetric nanofiltration (NF) flat sheet membrane was fabricated for acetic acid removal. Five types of asymmetric NF membranes were produced with different formulation in term of polymeric material (polysulfone (PSf) and polyethersulfone (PES)), types of solvent (N-methyl-2-pyrrolidone (NMP), tetrahydrofuran (THF), ethanol, dimethylacetamide (DMAc)), and types of additive (polyvinylpyrrolidone (PVP), polyethylene glycol (PEG)]. The best separation factor of acetic acid over glucose (1.1607) and acetic acid over xylose (1.2985) were showed by the asymmetric membrane produced from 19.6 wt% PSf/ 74.8 % DMAc/ 5.6 % ethanol and 21% PSf/ 55.3 % NMP/ 23.7 % THF.